Efek Multiplier Wakaf Uang Dan Pengaruhnya Terhadap Program Pengentasan Kemiskinan - Al Arif, M. Nur Rianto (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
One of the Islamic fiscal instrument is waqf that have been played a significant role in economics.  Cash waqf is a new instrument  in  the  field  of  waqf  and  Islamic  economics as a facility for the purpose of worship and to achieve social welfare. The  development  of  the  waqf  field  through  cash  waqf, management  which  is  flexible  and  offers  many  choices.  Cash waqf have the multiplier effect in economic,  through this effect cash  waqf  can  be  used  as  instrument  to  poverty  alleviation program through community empowerment program.